Marker assisted selection in agriculture - Paterson, Andrew H. (Henry Stewart Talks, 2013)
Measuring traits & genetic markers directly, Evolution of genetic markers, Discrete traits resulting from single genes, Marker searches using pooling strategies, Small influences of environment vs. dealing with complex traits, Quantitative trait locus (QTL) mapping, Association genetics complements QTL mapping, Conventional 3-generation linkage mapping, False positive (relatedness) vs. Significant association, Massively parallel sequencing, Cycling of gametes in vitro